Is negative urine culture necessary for PCNL safety? Experience from a large-volume stone center - Bo, Xiao; Zeng, Xue; Zhang, Gang; Ji, Chaoyue; Jin, Song; Bai, Wenjie; Tang, Yuzhe; Wang, Bixiao; Li, Jianxing (Frontiers in Surgery, 2025)
ObjectivesTo present our large single-center experience in managing patients with positive urine cultures and kidney stones with total ultrasound-guided percutaneous nephrolithotomy (PNL) and to redefine the role of urine culture in modifying these patients’ treatment plans.Patients and methodsWe retrospectively reviewed the charts of patients who had undergone PNL in our department from January 2016 to December 2020 and identified 422 eligible patients. These patients were allocated to two groups according to pre-operative urine culture results: negative (Group 1, n = 278) and positive (Group 2, n = 144). All procedures were ultrasound-guided. Standard access was achieved in all patients. Relevant patient characteristics, operative variables, and postoperative data were collected and analyzed, focusing on infection-related data, particularly sepsis.ResultsSuccessful renal access and stone fragmentation were achieved in all patients. At least one standard (24F) tract was established and a negative suction system introduced in every case. Escherichia coli was the most common bacterium in positive urine culture patients. Preoperative serum creatinine differed significantly between Groups 1 and 2 (1.2 ± 0.2 mg/dl vs. 2.0 ± 0.7 mg/dl, p = 0.02). Durations of surgery (79.2 ± 22.2 min) and post-operative hospitalization (7.6 ± 2.1 days) were longer in Group 2 than in Group 1 (58.2 ± 17.2 min) and (5.6 ± 1.1 days), respectively. Group 1 required fewer renal accesses than did Group 2 (1.1 ± 0.2 vs. 1.7 ± 0.2). The immediate stone-free rate was significantly greater in Group 1 (249; 89.2%) than in Group 2 (108; 75%).ConclusionsUltrasound guided PNL with standard access reveals a safe and acceptable results in positive urine culture patients. Preoperative infected urine is not a risk factor for severe septic complications after PNL under controlled conditions.